On common generalized inverses of a pair of matrices - Tian, Yongge; Takane, Yoshio (Linear & multilinear algebra, 2006)
Necessary and sufficient conditions are established for a pair of matrices of the same size to have a common {1}-inverse, {1, 2}-inverse, {1, 3}-inverse, {1, 4}-inverse, {1,2,3}-inverse and {1,2,4}-inverse, {1,3,4}-inverse, respectively. The relations between and are also investigated. In addition, some consequences and applications are given.